Ray George interviewed by Hazel de Berg for the Hazel de Berg collection - George, Ray.; De Berg, Hazel, 1913-1984. (1965)
George speaks of his academic background ; of his interest and research into the habits of the commercial crayfish.
Digital master available
Transcript available (3 p.)
Keywords: George, Ray -- Interviews; Marine biologists -- Australia -- Interviews